Development of Website-Based Learning Media Based on Learner Behaviorism - Ali, Nabila Nurhaliza; Rahayu, Diar Veni (Plusminus: Jurnal Pendidikan Matematika, 2024)
Penelitian ini untuk mengembangkan media pembelajaran berbasis web berdasarkan behaviorisme peserta didik SMP dalam mengasah kemampuan numerasi matematis, serta menguji kelayakan media pembelajaran. Menggunakan metode pengembangan R&D dengan model pengembangan luther-sutopo. Metode pengumpulan data yaitu survey. Instrumen penelitian yaitu lembar validasi. Teknik analisis data dengan mendeskripsikan tahapan pengembangan media web dengan model pengembangan luther-sutopo. Hasil analisis data menunjukkan tingkat kelayakan dari ahli materi sebesar 76,66% (kategori layak), ahli media sebesar 100% (sangat layak). Pada tahap uji coba beta didapatkan sebesar 95,33% termasuk kategori sangat layak. This study aims to develop web-based learning media based on junior high school students' behaviorism in honing mathematical numeracy skills and to test the feasibility of learning media. Using the R&D development method with the Luther-Sutopo development model. The data collection method is a survey. The research instrument is a validation sheet. Data analysis techniques by describing the stages of web media development with the Luther-Sutopo development model. The results of the data analysis show the level of feasibility from material experts of 76.66% (feasible category), and media experts of 100% (very possible). At the beta trial stage, 95.33% were obtained, including the very feasible category.